Return to dance following arthroscopic knee surgeries: what are the differences between return to sport and return to dance - Aksu, N.; Atansay, V.; Akgonul, B.; Ayaz, B.; Kara, A. N.; Hamzaoglu, A. (British Journal of Sports Medicine, 2021)
Background: Due to risk of reinjury and osteoarthritis, timing of return back to level 1 (jumping, pivoting and hard cutting) sports after surgeries is important. Dance injuries are much like sports injuries and literature is not available on the time to return to dance, rate of reinjury and osteoarthritis following arthroscopic surgery.